ANALISIS SEMIOTIKA CHARLES MORRIS DALAM LAGU SAYYIDI AR-RAIS KARYA HAMA MESHARY HAMADA - sherly Ulfa Umairoh (Fakultas Adab dan Humaniora UIN Imam Bonjol Padang, 2022)
This study aims to describe the meaning of the song Sayyidi Ar-Rais in the work of Hama Meshary Hamada using Charles Morris Semiotics analysis which divides the analysis into 3, namely Semantics, Pragmatics, and Syntax. The author uses descriptive qualitative research in describing the research data. The data taken from Zain Ramadhan Channel's youtube account was collected through several stages: first, the author documented the lyrics of the Sayyidi Rais song taken from the data source; second, the writer chooses several song stanzas as the corpus of analysis; third, the authors classify the data and determine the final data. The data were analyzed by Charles Morris's theory. The result of this research is that it can be concluded that the data analyzed by Charles Morris's theory has 3 divisions: Semantics, Pragmatics, and Syntax. In terms of semantics, the meaning of the quote in the song has a symmetrical relationship between the signifier and the signified. From a pragmatic point of view, it is found what the meaning of the speech in the quotes from Sayyidi Ar-Rais's song is. Meanwhile, in terms of syntax, the sentence structure of this song tends to be simple and conforms to the standard Arabic structure.